2015
DOI: 10.1002/jctb.4715
|View full text |Cite
|
Sign up to set email alerts
|

Key role of activated carbon fibers in enhanced decomposition of pollutants using heterogeneous cobalt/peroxymonosulfate system

Abstract: BACKGROUND The development of effective and green peroxymonosulfate (PMS) activation processes has attracted considerable attention and still remains a great challenge in the environmental field. Herein, the cobalt catalyst was innovatively supported onto activated carbon fibers (ACFs) to construct an outstanding heterogeneous catalyst, Co@ACFs, for PMS activation. RESULTS Co@ACFs could effectively activate PMS to decompose dyes with about 100% removal rate in 35 min. Co@ACFs maintained its catalytic ability w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…The concentrations of Mn, Co and Fe in the reaction mixture of the ‘Fe 3 O 4 @C/MnCo 2 O 4 + PSM’ system were determined by ICP as 0.07, 0.12 and 0.01 mg L −1 , respectively, which contributed to the metal leaching from Fe 3 O 4 @C/MnCo 2 O 4 . The levels of these ions in aqueous solution were comparable or lower than those leached from relevant oxides as reported in the literature . In order to investigate the possible contribution of the metal ions leached from the Fe 3 O 4 @C/MnCo 2 O 4 catalyst, the catalyst Fe 3 O 4 @C/MnCo 2 O 4 was separated when the reaction was finished and the remaining solution was used again to activate PMS for the removal of AO II.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…The concentrations of Mn, Co and Fe in the reaction mixture of the ‘Fe 3 O 4 @C/MnCo 2 O 4 + PSM’ system were determined by ICP as 0.07, 0.12 and 0.01 mg L −1 , respectively, which contributed to the metal leaching from Fe 3 O 4 @C/MnCo 2 O 4 . The levels of these ions in aqueous solution were comparable or lower than those leached from relevant oxides as reported in the literature . In order to investigate the possible contribution of the metal ions leached from the Fe 3 O 4 @C/MnCo 2 O 4 catalyst, the catalyst Fe 3 O 4 @C/MnCo 2 O 4 was separated when the reaction was finished and the remaining solution was used again to activate PMS for the removal of AO II.…”
Section: Resultsmentioning
confidence: 80%
“…Therefore, it is highly desirable to develop novel and recoverable heterogeneous catalysts to minimize heavy metal leaching while maintaining high performance PMS activation . For this purpose, investigations have been reported using cobalt oxides, manganese oxides, supported cobalt compounds, supported manganese compounds, and supported bimetallic catalysts such as Co‐Fe/SBA‐15 etc. as heterogeneous catalysts for the activation of PMS.…”
Section: Introductionmentioning
confidence: 99%
“…Huang et al reported that using activated carbon fiber as a cobalt support could facilitate electron transfer to improve catalytic activity of cobalt[48].Shi et al …”
mentioning
confidence: 98%
“…thereby accelerating the degradation kinetics[48]. Considering that Co 2+ ion is a benchmark catalyst to activate Oxone, Co 2+ ion of an equivalent amount to cobalt present in MCC was also tested and the corresponding degradation in shown inFig.…”
mentioning
confidence: 99%
“…[7][8][9] Recently, sulfate radicals (cSO 4 À ) have received intensive research interests as another powerful reactive radicals, because they can not only compensate some critical inadequacies of cOH, but also provide higher standard reduction potential (2.5-3.1 V) under neutral conditions than cOH (1.8-2.7 V). 10 It is well known that cSO 4 À can be released from peroxymonosulfate (PMS) or persulfate (PS) by heating, UV irradiation, ultrasonication, and catalytic activation, where catalytic activation has its own advantages without the assistance of necessary equipment and high-energy input.…”
Section: Introductionmentioning
confidence: 99%